Wom Marketing In The Age of Social Media: a Bibliometric Review and Vosviewer Visualization - Andriansyah; Situmorang, Syafrizal Helmi; Sembiring, Beby Karina Fawzeea (Forum Kerjasama Pendidikan Tinggi, 2024)
This study presents a bibliometric analysis of electronic word-of-mouth (eWOM) marketing to explore the development of this concept in the social media era. By referencing 267 articles sourced from the Scopus database from 2009 to 2023, this study employs bibliometric techniques, including citation analysis, co-citation analysis, and keyword co-occurrence analysis. Citation analysis helps identify the most influential and frequently cited articles, whereas co-citation and keyword co-occurrence analyses provide insights into the relationships between various studies and dominant research topics. This analysis revealed the trajectory and focal points of eWOM marketing research over the past 14 years. The study also identifies the most prominent authors, journals, institutions, and countries in eWOM literature. However, the use of a single database source may be a limitation of this study, suggesting that additional techniques and data sources are required for future research. For academics and practitioners, this study offers comprehensive insights into the eWOM concept, which can serve as a reference for strategic initiatives to drive customer purchasing behavior.